Media and Conflict
XXV, 264 p. 4 illus., 3 illus. in color.
Keywords: This book integrates critical studies of conflict news discourses and social media exchanges in India to discuss their underlying sociopolitical and economic ideologies and powerplays. Using several theoretical frameworks to investigate how assorted Indian conflicts are presented in the mediascape, the book aims to educate and empower audiences - and inspire the next generation of journalists to be constructively critical, ethical and peace-conscious. Francis Philip Barclay belongs to the Department of Media and Communication, Central University of Tamil Nadu (CUTN), India. Dr Barclay is an accomplished writer with a journalism and political cartooning background. His most recent book is Sexual Violence and Predatory Journalism in India (Routledge, UK, co-authored with Dr Laskar). Kaifia Ancer Laskar is from the Department of Journalism and Mass Communication, Aliah University, India. Dr Laskar was elected as the International Liason (2024-2026 term) in the Ethnicity and Race in Communication Division at the International Communication Association. Boobalakrishnan N belongs to the Department of Media and Communication, CUTN. His research interests include media, parenting and children, interpersonal communication, gerontechnology and cultural communication.